Ethical Considerations and Informed Consent in Anesthesiology - Sofi Showkat Saleem; Dr.Qumail Hussain; Shuja Abass (MEDALION Journal: Medical Research, Nursing, Health and Midwife Participation, 2026)
In anesthesiology, ethical principles such as autonomy, beneficence, non-malfeasance, and justice are critical. This paper investigates these ethical considerations, emphasizing the process of obtaining informed consent. It addresses the unique challenges in anesthesiology, including the effects of anesthesia on patient cognition, the complexity of information, and the urgency often associated with anesthesia in emergency settings. The paper explores the implications of these challenges on obtaining valid consent and offers strategies to improve informed consent practices. These strategies include enhancing communication, providing pre-operative education, and ensuring thorough documentation. By adhering to these practices, anesthesiologists can better respect patient autonomy, mitigate risks, and uphold ethical standards in their practice. The goal is to ensure that patients are fully informed and able to participate meaningfully in decisions about their anesthesia care, even in complex and time-sensitive situations.